2019
DOI: 10.1002/jgh3.12253
|View full text |Cite
|
Sign up to set email alerts
|

Hypereosinophilia‐related liver pseudotumor with elevated interleukin‐5 levels preceding T‐cell lymphoma

Abstract: A 61‐year‐old woman with hypereosinophilia and elevated interleukin (IL)‐5 level was admitted to our hospital after detection of multiple liver tumors. Liver biopsy demonstrated that the tumor consisted of scar tissue with remnants of eosinophilic infiltration, suggesting that it had formed by massive eosinophilic infiltration. The hypereosinophilia was treated mainly by prednisolone, and thereafter, the liver tumors disappeared. However, 10 months postadmission, CD4+ T‐cell lymphoma, which can produce IL‐5, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…When further analyzing the distribution of blood eosinophil counts in the internal and surgical departments, we observed that it was higher in the departments of hematology, rheumatology, and hepatological surgery, which could be closely related to some diseases in these departments. Some previous studies believed that the use of blood eosinophilic counts combined with other auxiliary diagnosis evidence can be of great help in the diagnosis of some complex diseases, which should receive greater attention in the future [ [21] , [22] , [23] , [24] ].…”
Section: Discussionmentioning
confidence: 99%
“…When further analyzing the distribution of blood eosinophil counts in the internal and surgical departments, we observed that it was higher in the departments of hematology, rheumatology, and hepatological surgery, which could be closely related to some diseases in these departments. Some previous studies believed that the use of blood eosinophilic counts combined with other auxiliary diagnosis evidence can be of great help in the diagnosis of some complex diseases, which should receive greater attention in the future [ [21] , [22] , [23] , [24] ].…”
Section: Discussionmentioning
confidence: 99%